2019
DOI: 10.1055/s-0039-1692973
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Transverse Cervical Artery and Vein for Complex Head and Neck Reconstruction

Abstract: Background Chemoradiotherapy is the primary treatment modality for glottic and pharyngeal subsites. Management of recurrence or second primaries in this setting is a surgical challenge requiring complex free flap reconstruction. One of the major barriers to effective reconstruction is the availability of suitable recipient vessels. We propose that the transverse cervical artery (TCA) is a viable option for complex head and neck reconstruction. Methods A retrospective chart review of 230 consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…18 These advantages are probably associated with the anatomi-cal characteristics of the TCA that protect it from the effects of radiation and neck dissection. 20 The clinical results of the current study also demonstrated the reliability of the TCA as a recipient vessel. The current study focused on total pharyngolaryngectomy and free jejunum transfer as an established reconstruction model in which both the TCA and the external carotid system provide candidate recipient vessels.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…18 These advantages are probably associated with the anatomi-cal characteristics of the TCA that protect it from the effects of radiation and neck dissection. 20 The clinical results of the current study also demonstrated the reliability of the TCA as a recipient vessel. The current study focused on total pharyngolaryngectomy and free jejunum transfer as an established reconstruction model in which both the TCA and the external carotid system provide candidate recipient vessels.…”
Section: Discussionsupporting
confidence: 63%
“…18 These advantages are probably associated with the anatomical characteristics of the TCA that protect it from the effects of radiation and neck dissection. 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation